2022
DOI: 10.3389/fcvm.2021.795747
|View full text |Cite
|
Sign up to set email alerts
|

p53 SUMOylation Mediates AOPP-Induced Endothelial Senescence and Apoptosis Evasion

Abstract: The aging of endothelial cells plays a critical role in the development of age-related vascular disease. We established a model of endothelial premature senescence by application of Advanced oxidation protein products (AOPPs) modified bovine serum albumin (AOPP-BSA) in human umbilical vein endothelial cells (HUVECs). This cellular senescence was accompanied with endothelial barrier dysfunction and angiogenesis impairment. It was further revealed that these senescent HUVECs underwent apoptosis evasion and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…As stated, PIASy was important in terms of its ability to regulate Cav-3 SUMOylation in response to I/R stimulation. Similar roles for PIASy were reported in regulating specific molecules, including von Hippel-Lindan [35], NF-kappaB essential modulator [36], p53 [37], and Tat-interacting protein 60 [38] in response to different cellular environments.…”
Section: Discussionsupporting
confidence: 65%
“…As stated, PIASy was important in terms of its ability to regulate Cav-3 SUMOylation in response to I/R stimulation. Similar roles for PIASy were reported in regulating specific molecules, including von Hippel-Lindan [35], NF-kappaB essential modulator [36], p53 [37], and Tat-interacting protein 60 [38] in response to different cellular environments.…”
Section: Discussionsupporting
confidence: 65%
“…High levels of glucose or other reducing sugars can introduce advanced glycation end-products (AGEs) into the circulation 72 , and these AGEs can bind to and stimulate ECs, generating ROS 73 . Similarly, the levels of advanced oxidation protein products (AOPPs), which can be increased by AGEs, tend to be high in uremic patients and have been shown to induce senescence in HUVECs 74 . Other substances, such as circulating microparticles (MPs), which are shed from the membrane following a variety of stimuli and are circulated through the bloodstream 75 , can lead to endothelial dysfunction by mediating NO and ROS production 76 , 77 .…”
Section: Endothelial Senescence In Vascular Diseasesmentioning
confidence: 99%
“…Advanced oxidation protein products (AOPPs) result from cell oxidative stress and are accumulated and increased in patients with vascular disease and aging ( 153 ). In HUVECs, AOPPs induced senescence, increasing the expression of p21, p16 and SA β-gal activity, along with an impairment in autophagic flux ( 154 ). The effects of AOPPs were also evaluated in a model of ApoE -/- mice fed with a HFD, which showed an increase in senescence molecular markers in aortic tissue ( 154 ).…”
Section: Autophagy Cell Senescence and Vascular Agingmentioning
confidence: 99%
“…In HUVECs, AOPPs induced senescence, increasing the expression of p21, p16 and SA β-gal activity, along with an impairment in autophagic flux ( 154 ). The effects of AOPPs were also evaluated in a model of ApoE -/- mice fed with a HFD, which showed an increase in senescence molecular markers in aortic tissue ( 154 ). Interestingly, it has been reported that autophagy reduces apoptosis and senescence induced by high glucose concentrations in human coronary artery ECs ( 155 ).…”
Section: Autophagy Cell Senescence and Vascular Agingmentioning
confidence: 99%
See 1 more Smart Citation